2017
DOI: 10.1111/jocn.13429
|View full text |Cite
|
Sign up to set email alerts
|

The experience of people with dementia and nurses in hospital: an integrative review

Abstract: Nurses must understand the complex needs of people with dementia in hospital. Nurse education about dementia, practical support, strong clinical leadership and role-modelling is needed. Empathy for patients regardless of diagnosis must remain a core attribute of nurses. Current hospital culture requires wider system review to mitigate against stigmatisation of patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
159
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 53 publications
(429 reference statements)
10
159
0
1
Order By: Relevance
“…The findings show that caring for PwD in acute settings is always accompanied by great uncertainty for nurses and that individual nurses react in different ways to address their uncertainty. The findings reinforce earlier studies that reported that caring for people with cognitive impairment in acute care settings is complex and challenging and that there are different barriers to ensuring appropriate care for PwD (Digby et al., ; Houghton et al., ; Turner et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…The findings show that caring for PwD in acute settings is always accompanied by great uncertainty for nurses and that individual nurses react in different ways to address their uncertainty. The findings reinforce earlier studies that reported that caring for people with cognitive impairment in acute care settings is complex and challenging and that there are different barriers to ensuring appropriate care for PwD (Digby et al., ; Houghton et al., ; Turner et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…As mentioned previously, the Japanese government introduced financial benefits in the form of paid medical fees for the appropriate and effective care of patients with dementia in acute care hospitals. However, many nurses feel that patients with dementia disrupt the normal hospital routine and create an obstacle in the delivery of medical care to other patients (Digby, Lee, & Williams, ). In acute hospitals in particular, where nurses need to address the needs of many patients simultaneously, the staff considers the care of patients with dementia to be “troublesome” (Featherstone, Northcott, & Bridges, ).…”
Section: Discussionmentioning
confidence: 99%
“…They are also more likely to be discharged to a care home resulting in further financial costs for local health and social care services (Connolly & O’Shea, ). People living with dementia in hospitals and their family caregivers have reported negative experiences of hospital stay (Digby, Lee, & Williams, ). Qualitative studies have shown that acute care staff find it difficult to deliver person‐centred dementia care (Clissett, Porock, Harwood, & Gladman, ) and meet the holistic needs of their patients (Scerri, Innes, & Scerri, ).…”
Section: Introductionmentioning
confidence: 99%